Tracking B-31 iceberg with two aircraft-deployed sensors - D. H. Jones; G. H. Gudmundsson (Natural Hazards and Earth System Sciences, 2015)
Icebergs are a natural hazard to maritime operations in polar regions. Iceberg populations are increasing, as is the demand for access to both Arctic and Antarctic seas. Soon the ability to reliably track icebergs may become a necessity for continued operational safety. The temporal and spatial coverage of remote sensing instruments is limited, and must be supplemented with in situ measurements. In this paper we describe the design of a tracking sensor that can be deployed from a fixed-wing aircraft during surveys of Antarctic icebergs, and detail the results of its first deployment operation on iceberg B-31.